Das Verhalten holomorphen im Kreise Lösungen einer Differentialgleichung erster Ordnung - Nagelė, A.; Strelitz, S. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:А. В. Нагяле, Ш. И. Стрелиц. Поведение голоморфных в круге решений дифференциальных уравнений первого порядкаA. Nagelė, S. Strelicas. Pirmos eilės diferencialinių lygčių holomorfinių sprendinių elgimasis skritulyje